The Effect of Google Classroom Media Utilization in Physics Learning on Students' Interest and Learning Outcomes at SMA Negeri 9 Kendari - La Isa; Santri Santri; Zainuddin zainuddin; La Ode Asmin; Dewi Santri (Universitas Islam Negeri (UIN) Mataram, 2023)
This study aims to determine the effect of Google Classroom media utilization in learning Physics on students' interest and learning outcomes at SMA Negeri 9 Kendari. The method used in this research is an ex post facto survey with a quantitative approach. The data analysis technique used is path analysis with the help of Smart-PLS software at α = 5%. Based on the study results, it is concluded that the utilization of Google Classroom is classified in the excellent category with a percentage figure of 69.59%. Learning interest is organized in a strong class with a percentage rate of 75.55%. Learning outcomes are classified in the moderate category with an average acquisition value of 73.62 and a percentage rate of 100% of students meeting the minimum completeness criteria (KKM). Google Classroom utilization (X) significantly affects learning interest (Y1) by 0.559. Google Classroom utilization can explain/contribute to students' physics learning outcomes by 13%. Google Classroom utilization (X) has a significant indirect effect on learning outcomes (Y2) through learning interest (Y2) of 0.240. Google Classroom utilization can explain/contribute to students' physics learning outcomes.